2018
DOI: 10.7150/ijms.25687
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Orosomucoid A Potential Marker Of Inflammation In Psoriasis

Abstract: Background: Psoriasis is one of the most common chronic, life-long dermatologic diseases, which has considerable negative effects on quality of life. Psoriasis is considered as a systemic inflammatory disease, thus acute phase proteins such as C-reactive protein (CRP) and orosomucoid (ORM) have been shown to play a role in its pathophysiology. This study was aimed to compare CRP, serum ORM (se-ORM) and urinary ORM (u-ORM) levels of psoriatic patients to healthy individuals.Methods: 87 psoriatic patients and 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 30 publications
6
17
1
1
Order By: Relevance
“…However, the levels of non-specific inflammatory markers (s-ORM and CRP) were significantly higher in patients suffering from severe psoriasis compared to mild psoriatic patients. This indicates that in the case of severe psoriatic patients some grade of systemic inflammation is present 9,45. In our previous study, both u-ORM and u-ORM/u-CREAT ratio were significantly higher in psoriatic patients compared to controls 45.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, the levels of non-specific inflammatory markers (s-ORM and CRP) were significantly higher in patients suffering from severe psoriasis compared to mild psoriatic patients. This indicates that in the case of severe psoriatic patients some grade of systemic inflammation is present 9,45. In our previous study, both u-ORM and u-ORM/u-CREAT ratio were significantly higher in psoriatic patients compared to controls 45.…”
Section: Discussionmentioning
confidence: 75%
“…This indicates that in the case of severe psoriatic patients some grade of systemic inflammation is present 9,45. In our previous study, both u-ORM and u-ORM/u-CREAT ratio were significantly higher in psoriatic patients compared to controls 45. Taking this into account, u-ORM and u-ORM/u-CREAT ratio could be used as an indicator of low-grade inflammation or oxidative stress in mild and moderate psoriasis, as other biomarkers investigated in this study were not able to indicate significant inflammation or excessive oxidative stress in the case of mild and moderate psoriatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Kustán et al [79], in a study conducted in Hungary in patients with psoriasis, measured the levels of water-phase proteins, such as high-specificity reactive C-protein (hsPCR) and orosomucoid in serum and urine (sepsis; ORM and u-ORM). To perform the study, 87 patients were used with levels of mild, moderate, and severe psoriasis and 41 healthy patients as controls.…”
Section: Association Between Some Obesity Biomarkers and Psoriasismentioning
confidence: 99%
“…ORM proteins could be applied as diagnostic markers for the early events of many pathological states. Elevated urinary ORM levels have been reported as biomarkers for multiple carcinomas and inflammatory diseases such as psoriasis, Crohn disease, and sepsis (39)(40)(41)(42)(43). Notably, Park et al (44) demonstrated that the urinary levels of ORM1 and ORM2 were increased in patients with RA and correlated with disease activity.…”
Section: Discussionmentioning
confidence: 99%